Kajian Filosofis tentang Peranan Guru PAK:: Tinjauan Ontologis, Epistemologis, dan Aksiologis - Tanama, Yulia Jayanti; Supit, Sugijanti; Wariki, Valentino; Monica Halawa, Agnes (Sekolah Tinggi Teologi Kalvari Manado, 2025)
Abstract: Teachers play an important role in the success of learning, which requires philosophy. However, philosophy is considered unimportant and boring, and is not visible in dealing with educational issues. This study aims to analyze the role of Christian Religious Education teachers from an ontological, epistemological, and axiological perspective to provide a comprehensive and in-depth understanding of the nature, sources of knowledge, and values inherent in the role of teachers. The method used in this study is literature research through the process of collection, analysis, and synthesis. The results of this study are that the role of Christian Religious Education teachers ontologically is as the image of God, servants and instruments of God, and a calling in life. Epistemologically, the role of Christian Religious Education teachers is as guides, facilitators, and interpreters. Axiologically, the role of Christian Religious Education teachers is as planters of Christian values, role models, and character builders. Abstrak: Guru memegang peranan penting untuk menyukseskan suatu pembelajaran dalam perjalanannya membutuhkan filsafat. Tetapi filsafat dianggap tidak penting dan membosankan serta tidak terlihatnya dalam menangani masalah pendidikan. Penelitian ini bertujuan untuk menganalisis peran guru Pendidikan Agama Kristen dalam perspektif ontologi, epistemologi, dan aksiologi untuk memberikan pemahaman secara menyeluruh dan mendalam mengenai hakikat, sumber pengetahuan, serta nilai yang melekat pada peran guru. Metode yang digunakan dalam penelitian ini adalah penelitian literatur melalui proses pengumpulan, analisis, dan sintesis. Hasil penelitian ini adalah peran guru Pendidikan Agama Kristen secara ontologi sebagai imago dei, pelayan dan alat Tuhan, serta panggilan hidup. Secara epistemologis, peran guru Pendidikan Agama Kristen sebagai pembimbing, fasilitator, dan pengarah serta penafsir. Secara aksiologi, peran guru Pendidikan Agama Kristen sebagai penanam nilai-nilai Kristiani, teladan, dan pembentuk karakter.